2016
DOI: 10.1016/j.yhbeh.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of bisphenol A (BPA) and soy phytoestrogens on sexually dimorphic sociosexual behaviors in male and female rats

Abstract: Concerns have been raised regarding the potential for endocrine disrupting compounds (EDCs) to alter brain development and behavior. Developmental exposure to bisphenol A (BPA), a ubiquitous EDC, has been linked to altered sociosexual and mood-related behaviors in various animal models and children but effects are inconsistent across laboratories and animal models creating confusion about potential risk in humans. Exposure to endocrine active diets, such as soy, which is rich in phytoestrogens, may contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
14
1
Order By: Relevance
“…Animals were assessed for general activity and anxiety-related behavior as juveniles or as adults (no animals were tested at both ages) using standard procedures (see Supplemental Materials for more detail). For all tests except the running wheel, animals were transported down a short hallway to a nearby testing room on a covered rolling cart and tested after a short acclimation period, as we have done previously 26 , 33 , 39 . Testing was conducted within the first 4 hours of the dark cycle, recorded, and subsequently analyzed by TopScan software (Clever Sys Inc., Reston, VA) by observers blinded to exposure group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animals were assessed for general activity and anxiety-related behavior as juveniles or as adults (no animals were tested at both ages) using standard procedures (see Supplemental Materials for more detail). For all tests except the running wheel, animals were transported down a short hallway to a nearby testing room on a covered rolling cart and tested after a short acclimation period, as we have done previously 26 , 33 , 39 . Testing was conducted within the first 4 hours of the dark cycle, recorded, and subsequently analyzed by TopScan software (Clever Sys Inc., Reston, VA) by observers blinded to exposure group.…”
Section: Methodsmentioning
confidence: 99%
“…Juvenile testing spanned PNDs 24–28 to ensure females would be tested prior to vaginal opening (pubertal onset) 26 . The same juvenile rats, one per sex per litter, were tested in two apparatuses: light/dark box (L/D; control: 10♀, 7♂, low: 7♀, 8♂, mid: 9♀, 8♂, high: 9♀, 6♂) and open field (OF; control: 8♀, 7♂, low: 7♀, 7♂, mid: 7♀, 6♂, high: 7♀, 5♂) using well-established methods as previously described by us and others 33 , 39 . Two main endpoints were used to assess anxiety-like behavior in the L/D box: latency to enter the light side and the number of entries made into the light side within the 10 minute testing period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggest that early exposure to GEN or phyto‐oestrogens in general can affect later social behaviours. A study with male and female rats found that, although BPA did not affect social and activity levels, GEN in a soy‐enriched diet suppressed novelty preference and open field exploration in females at postnatal days 24‐28 82 . Perinatal exposure of male mice to GEN led to significant changes in anxiety and aggressive behaviours 83 .…”
Section: Discussionmentioning
confidence: 99%
“…These males had reduced number of positively stained cells in the amygdala neuronal cells staining positive for nitric-oxide synthase. A similar GEN exposure dose and period to Wistar rats resulted in sex-specific offspring effects with females displaying reduced novelty preference and exploration in an open field maze (41). On the other hand, developmental exposure to GEN (soy based diet, Purina 5001) from gestation through puberty has been suggested to abolish bisphenol A (BPA)-induced effects on anxiogenic behaviors in juvenile Wistar rats and restore normal sex differences in exploratory behavior in these animals (42).…”
Section: Animal Model Studies Reporting Neurobehavioral Effects Follomentioning
confidence: 99%